THE PROMISE AND CAVEATS OF IMPLEMENTING DISCOVERY-INQUIRY - Nurdin, Enjang Ali (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2018)
Discovery learning is arguably the most debated learning approach because even after more than 58 years since Brunner suggested it in 1961, it continued to be a center of heated debate. The main concern for numerous educational experts was the degree of teacher involvement in discovery learning. One of the discovery learning variants which addressed this issue is discovery-inquiry learning, a learning model currently endorsed by the Indonesian Government to be implemented in the classroom. This study explored the potency and caveats of discovery-inquiry learning model and discussed improvement suggestions when implementing the model.